m5C Regulator-mediated methylation modification clusters contribute to the immune microenvironment regulation of multiple myeloma - Ren, Hefei; Liu, Chang; Wu, Hongkun; Wang, Zhenhua; Chen, Sai; Zhang, Xiaomin; Ren, Jigang; Qiu, Huiying; Zhou, Lin (Frontiers in Genetics, 2022)
Abstract Background: Multiple myeloma (MM) is a hematological malignancy in which plasma cells proliferate abnormally. 5-methylcytosine (m5C) methylation modification is the primary epigenetic technique and is involved in regulating the occurrence, development, invasion, and metastasis of various tumors; however, its immunological functions have not been systematically described in MM. Thus, this study aimed to clarify the significance of m5C modifications and how the immune microenvironment is linked to m5C RNA methylation in MM. Method: A total of 483 samples (60 healthy samples, 423 MM samples) from the Gene Expression Omnibus dataset were acquired to assess the expression of m5C regulators. A nomogram model was established to predict the occurrence of MM. We investigated the impact of m5C modification on immune microenvironment characteristics, such as the infiltration of immunocytes and immune response reactions. We then systematically evaluated three different m5C expression patterns to assess immune characteristics and metabolic functional pathways and established m5C-related differentially expressed genes (DEGs). In addition, biological process analysis was performed and an m5C score was constructed to identify potentially significant immunological functions in MM. Result: Differential expressions of m5C regulators were identified between healthy and MM samples. The nomogram revealed that m5C regulators could predict higher disease occurrence of MM. We identified three distinct m5C clusters with unique immunological and metabolic characteristics. Among the three different m5C clusters, cluster C had more immune characteristics and more metabolism-related pathways than clusters A and B. We analyzed 256 m5C-related DEGs and classified the samples into three different m5C gene clusters. Based on the m5C and m5C gene clusters, we calculated m5C scores and classified each patient into high- and low-m5C score groups. Conclusion: Our study demonstrated that m5C modification is involved in and contributes to the diversity and complexity of the immune microenvironment, which offers promise for the development of accurate therapeutic strategies.